Use of Parametric 3D Modelling - Tying Parameter Values to Spreadsheets at Designing Molds for Plastic Injection - Fabian, Michal; Boslai, Róbert; Ižol, Peter; Janeková, Jaroslava; Fabianová, Jana; Fedorko, Gabriel; Božek, Pavol (Manufacturing Technology Journal, 2015)
The current mechanical engineering is inconceivable without the implementation of CAx systems in design and manufacturing process of individual components. The automotive industry is a clear evidence of how CAx systems affect the innovation cycle of its product - a car. The innovation cycle in automotive was reduced from 8-12 years to the current 4-6 years. Even in this short interval automakers make some small design modifications called a facelift. Development in the automotive industry, therefore, is closely related to news and functionality CAx systems. CAD systems at the turn of the millennium are characterized as parametric graphic systems with a history tree of product creation. Parametric design implemented into CAD systems makes the model variable and open to rapid change management. The history tree in turn enables rapid editing and modification of forming or editing functions.
Keywords: CAD; 3D; parametric modeling; mold